Synthesis and antiproliferative evaluation of oxime, methyloxime, and amide‐containing quinazolinones. Issue 9 (22nd May 2018) - Chang, Ken‐Ming; Chen, Li‐Chai; Tzeng, Cherng‐Chyi; Lu, Yao‐Hua; Chen, I‐Li; Juang, Shin‐Hun; Wang, Tai‐Chi
Abstract : Certain oxime, methyloxime, and amide‐containing quinazolinone derivatives were synthesized and evaluated in vitro for their antiproliferative activities against a panel of human cancer cell lines including nasopharyngeal carcinoma (NPC‐TW01), lung carcinoma (NCI‐H226), and leukemia (Jurkat). Quinazolinone2 was inactive against all three cell lines tested, while quinazolinone4 was weakly active against both Jurkat and H226 cancer cells with IC50 values of 6.55 and 12.27 μM, respectively, indicating that the oxime derivative4 is more favorable than its ketone precursor2 . Our results have also indicated that quinazolinone8g and its biphenyl counterpart8f exhibited more potent antiproliferative activities than the positive control methotrexate against all three cancer cell lines tested. Among these quinazolinone derivatives, 8g was the most active against NPC‐TW01 with an IC50 value of 4.78 μM. Further study on NPC‐TW01 cell cycle distribution indicated that the compound8g induced cell arrest at the G1/G0 phase in a time‐ and concentration‐dependent manner. Moreover, a characteristic hypo‐diploid DNA content peak (sub‐G1) was found to increase from 1 to 4% in NPC‐TW01 cells treated with8g for 72 hr. These results indicate that8g can induce cells arrest in the G1/G0 phase and cause cell death. Further structural optimization of8g and detailed study of its antiproliferative mechanism are going on. Abstract : Certain oxime, methyloxime, and amide‐containing quinazolinone derivatives were synthesized and evaluated for their antiproliferative activities. Among them, the quinazolinone derivative8g was the most active against NPC‐TW01 with an IC50 value of 4.78 μM. Further study on cell cycle distribution indicated that compound8g induced cell arrest at the G1/G0 phase in a time‐ and concentration‐dependent manner.